Between Hip Hop and Me: Podcast Process Texts as Tools of Cultural Brokerage for Community Cultural Wealth. Issue 1 (November 2022) - Griffith, Jason J.; Celaya, Anthony S.; Sweet, Joseph D.
This research features a discourse analysis of two podcasts: the "Mobb Deep, Shook Ones, Pt. II" episode of Song Exploder and the "Rap on Trial" episode of Hidden Brain . We selected these podcasts through an abductive method of what we call "fortuitous listening" because of how they reveal community cultural wealth (CCW) through their descriptions of the creative process. Specifically, our study addressed two questions: (1) What does an examination of two Hip Hop podcast process texts reveal about CCW? (2) How could a discussion of the CCW that is revealed through descriptions of creative process inform literacy practices? Findings demonstrate how linguistic, familial, navigational, and aspirational capital exhibited in first-person descriptions of rap composition helped to showcase Hip Hop texts as what Bettina Love calls a "complex personhood" well-beyond simplified or stereotypical critiques. Because of how these process texts demonstrate the ways that Hip Hop feature Alim's ill-literacies criteria of being based on intimate, lived, and liberatory experiences, we posit them to be effective tools of cultural brokerage, particularly for educators wishing to enact Hip Hop-Based Education.